Comparison of Visual Outcomes Between Toric Intraocular Lenses and Clear Corneal Incisions to Correct Astigmatism in Image–Guided Cataract Surgery - Ding, Ning; Song, Xudong; Wang, Xiaozhen; Wei, Wenbin (Frontiers in Medicine, 2022)
Purpose To compare the astigmatism correction effects of toric intraocular lenses (IOL) and clear corneal incisions during image-guided cataract surgery. Methods All patients with regular corneal astigmatism of 0.75–1.5 D underwent cataract surgery and astigmatism correction using the Callisto eye image-guided system. One group had implantation of an AcrySof toric IOL. Another group had implantation of aspheric IOL with 3.0 mm single clear corneal incision (SCCI) on the steep axis. Uncorrected and best-corrected spectacle visual acuity, refraction, and toric IOL axis were evaluated at 1, 4, and 12 weeks postoperatively. Results Sixty-eight eyes of 68 patients were included. The mean residual refractive cylinder was 0.34 ± 0.40 D in the toric group and 0.64 ± 0.57 D in the SCCI group. There were no significant differences in residual refractive cylinder, spherical equivalent, uncorrected distance visual acuity (UDVA), and best-corrected spectacle visual acuity (BCSVA) between groups. The percentage of the residual cylinder within ± 0.50 D was 75 and 56% for toric and SCCI cases, respectively (p > 0.1). The mean surgical induced astigmatism vector was 0.61 ± 0.29 D in the SCCI group and 1.04 ± 0.38 D in the toric group. The mean magnitude of error was negative (−0.54 ± 0.48 D) and the correction index was <1.0 (p < 0.05) in SCCI group. At 3 months, all toric IOL alignment errors were within 5 degrees from the intended axis. Conclusions Both toric IOL and SCCI can correct low and medium astigmatism effectively with the help of a precise image-guided system.